Optimum size of government intervention: Emerging economies and their challenges - Das, Ramesh Chandra, 1973- (London : Routledge India, 2021)
This book critically examines the optimum range and duration of government interventions in the economic activities of a modern state based on theoretical and empirical frameworks, and assesses their role and extent in various economies. With a special focus on emerging economies across the globe, it discusses themes such as income growth; social sector development; good governance and economic progress; threshold limits; optimum budget policy and economic growth; sustainable distributional managements in public projects; food for work programs; agricultural infrastructure development; technological progress and economic growth; and distributional equities. The policy suggestions provided here offer helpful blueprints for developmental projects. Rich in data and figures, the book addresses sector-specific case studies like healthcare; irrigation and agriculture; infrastructure; taxation and economic growth; and public sector enterprises. It will be an excellent read for scholars and researchers of economics, Indian economics, macroeconomics, political economy, public policy, political science and management, development studies, development economy and governance. It will also be useful to policymakers, administrative officials, and government and corporate bodies.
Description based upon print version of record.
OCLC-licensed vendor bibliographic record.
Keywords: Economic development -- Developing countries; Economic development -- Government policy -- Developing countries; BUSINESS & ECONOMICS / Development / Economic Development; BUSINESS & ECONOMICS / Development / General; BUSINESS & ECONOMICS / Economics / General; Developing countries -- Economic policy